The impact of digital technologies and social networks in young women and young mother’s entrepreneurship and employability - Karyotaki , Maria; Drigas, Athanasios (Technium Sustainability, 2022)
Young mothers face various obstacles in the labour market due to lack of skills in job search techniques, unpaid domestic labour responsibilities and, in developing countries, social isolation and restrictions. Business training programs targeting young mothers must be demand-driven and linked with private sector labour demands. In addition, life skills training programs aiming at work and life balance combined with the provision of childcare, are measures that if taken, can enhance young mothers’ entrepreneurship. Except for entrepreneurial program curricula, special attention should be given to the dissemination and implementation methods of lifelong learning programs in order to be able to reach young mothers where they are.